Association of IKZF1 and CDKN2A gene polymorphisms with childhood acute lymphoblastic leukemia: a high-resolution melting analysis - Mahla Sattarzadeh Bardsiri; Shahrzad Zehtab; Najibe Karami; Alireza Farsinejad; Mohsen Ehsan; Ahmad Fatemi (BMC, 2022)
Abstract Background Acute lymphoblastic leukemia is the most prevailing pediatric hematologic malignancy, and various factors such as environmental exposures and genetic variation affect ALL susceptibility and patients outcome. According to genome-wide association studies, several single nucleotide polymorphisms (SNPs) in IKZF1 (rs4132601) and CDKN2A (rs3731249 and rs3731217) genes are associated with ALL susceptibility. Hereupon, this study aimed to discover the association between these SNPs and the risk of childhood ALL among a sample of the Iranian population. Methods A total of fifty children with ALL were included in this case-control study, along with an additional fifty healthy children, matched for age and gender. High-resolution melting (HRM) analysis was employed to genotyping rs4132601, rs3731249, and rs3731217. Results In the patient group, the CT genotype and T allele frequency of rs3731249 were significantly greater than controls (p = 0.01 and p = 0.005, respectively). Moreover, the positive association of CT and dominant model (CT + TT) genotypes and T allele at rs3731249 with the risk of ALL was confirmed (OR = 9.56, OR = 10.76 and OR = 11.00, respectively). There was no significant relation between rs4132601 (IKZF1), rs3731217 (CDKN2A), and childhood ALL. Conclusion The present study indicates that CT genotype and T allele at rs3731249 (CDKN2A) can significantly increase the risk of ALL among children.